2014
DOI: 10.5935/1676-2444.20140015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uropathogens and antimicrobial susceptibility profile in outpatient from Jataí-GO

Abstract: Introduction: Urinary tract infections (UTIs) affect people worldwide. Escherichia coli is the main agent of UTI, however the etiology may vary according to the age and sex of the patient. Regional variations in the prevalence and antimicrobial resistance should be considered for therapy choice. Objectives: This study aimed to conduct a survey on the main agents of UTI, and assess the resistance of these microorganisms, during the period of March 2010 to June 2012 in the city of Jataí-GO. Method: A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
0
1
0
6
Order By: Relevance
“…Sex was one of the considered factors and the result indicated that UTI prevalence was higher in females than males for each isolate. Previously, [ 25 , 39 , 40 ] have shown that incidence of UTI was found to be higher in females than in males. This is probably due to multiple factors contributing to the problems among females.…”
Section: Discussionmentioning
confidence: 99%
“…Sex was one of the considered factors and the result indicated that UTI prevalence was higher in females than males for each isolate. Previously, [ 25 , 39 , 40 ] have shown that incidence of UTI was found to be higher in females than in males. This is probably due to multiple factors contributing to the problems among females.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, essa variação nos índices de infecção pode estar relacionada com o nível de desenvolvimento do país e cultura de segurança do paciente. [10][11][12] O crescimento bacteriano inicia-se após a instalação do cateter, numa proporção de 5 a 10% ao dia, e estará presente em todos os pacientes ao final de quatro semanas. O potencial risco para ITU associada ao cateter intermitente é inferior, 3,1%, e na ausência de cateter vesical, 1,4%.…”
Section: Discussionunclassified
“…A coleta de dados ocorreu de janeiro de 2013 a dezembro de 14 Em relação aos microrganismos isolados dos casos de ITU-RC, o mais prevalente foi a Escherichia coli (32 %), corroborando os resultados de outros estudos. 10 Estudos brasileiros e internacionais identificam E. coli como o principal agente etiológico dessas infecções, com taxas de prevalência que variam entre 60% e 90%. 9, [15][16][17] O tempo de permanência na UTI foi outro fator preditor para ITU-RC.…”
Section: Introductionunclassified
“…Este é um estudo retrospectivo documental que avaliou os resultados das culturas de urina no serviço de obstetrícia de um hospital secundário localizado no município de Research, Society and Development, v. 9, n. 8, e862986337, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.6337 (Schnarr e Smaill, 2008;Moraes et al 2014;Foxman, 2014;Ballesteros-Monrreal, 2020;Omidifar et al, 2020). Essa alta frequência pode ser explicada pelo fato de sua presença estar relacionada à eliminação fecal e, consequentemente, à contaminação do trato urinário.…”
Section: Metodologiaunclassified